Hegel on Social Progress - Luneckas, Balys (Problemos, 1972)
According to the Hegelian conception of the history of philosophy, social progress is found (though in a mystified way) to be an objective and natural process. The latter is realized as a dialectical alteration of indispensable stages where every preceding step is considered to make an objective basis for conscious activities of people in a subsequent stage. Thus, the contents and criteria of social progress can be established not through abstract consideration and subjective desire, but through a specific analysis and comparison of the above stages.